Study Of Production And Strategy For Strengthening The Institution Of Livestock Commodities In Riung District - Tian Ngiso Bhae (Jurnal Ternak, 2026)
Riung District has abundant natural resource potential in the agriculture, livestock, and fisheries sectors, while also being an important ecosystem area that is vulnerable to damage. To date, the utilization of these commodities is often suboptimal and tends to ignore the principles of environmental sustainability due to weak local group governance. Therefore, institutional strengthening is a key factor in bridging the gap between improving community economic welfare and ecosystem sustainability. This study aims to analyze the existing condition of local institutions in the livestock sector in Riung District, as well as formulate adaptive institutional strengthening strategies to support efforts to conserve natural resources and the surrounding ecosystem. This study uses a qualitative-descriptive approach. Data were collected through field observations, in-depth interviews with farmers and the local government, and Focus Group Discussions (FGDs). Data analysis was carried out using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to map the internal and external factors of the institution. The results show that the existing institution (Livestock Group) still faces constraints in management capacity, limited market access, and low collective awareness of environmental conservation. The main strategies formulated include: (1) Increasing the human resource capacity of institutional administrators through training based on eco-farming and environmentally friendly fishing; (2) Integrating customary/local rules (local wisdom) into group regulations to limit the exploitation of natural resources; and (3) Creating a partnership network between local institutions with the private sector and government for value-added post-harvest management. Institutional strengthening that focuses on increasing internal capacity and implementing environmentally based regulations has proven crucial. Through strong institutions, the utilization of agricultural, livestock, and fishery products in Riung District can go hand in hand with maintaining ecosystem stability and long-term natural resource sustainability.